Assessment of knowledge, attitude and perceptions regarding kidney donation among nursing students at the University of Rwanda - Marie Louise Uwingabiye; Vedaste Baziga; Geldine Chironda; Lakshmi Rajeswaran (Elsevier, 2021)
Introduction: Kidney dysfunction and failure account for increased mortality rates across most population groups globally. Kidney donation and transplantation is a process whereby individuals agree to donate a healthy organ that is then transplanted to a recipient with either a damaged, failed or dysfunctional organ to save their life and improve their quality of life. Currently, there is very little published evidence on the knowledge, attitude and perceptions regarding organ donation among nurses in Rwanda. Therefore, this study was conducted to explore the knowledge, attitudes and perceptions regarding organ donation among nursing students at the University of Rwanda. Methods: A cross-sectional study design using a quantitative approach was adopted to explore the knowledge, attitudes and perceptions regarding organ donation among 179 nursing students at the University of Rwanda. The relationships between knowledge, attitude, perceptions regarding organ donation and socio-demographic characteristic variables were analyzed quantitatively reported using chi-squared tests with the level of significance set at P ≤ 0.05. Results: Overall, 51% of study participants reported a low level of knowledge on kidney donation. Attitudes were reported to be negative in 63% of cases and no association was found between knowledge and attitude toward kidney organ donation. Among the study participants, 68.6% reported that they would prefer to donate their organ to a family member, while 36.9% believed that the recipient being a family member is the most important factor to consider in deciding to donate their organ in the case of need. Conclusion and recommendation: This study revealed an unsatisfactory level of knowledge and negative attitude of nursing students toward organ donation. This is an important issue since these future nurses will be expected to support kidney donation in one way or another. Interventions to change the current situation are urgently needed.